Venturing into the Chinese market : a study of effective business venturing strategies for Singapore SMEs - Chang, Tino Shu Hao. (2008)
Outline the effectiveness of current assistances given by Singapore government, summarise various market entering modes available, analyse current business formation practices, discuss various marketing tools available and ultimately develop and establish a model for Singapore companies which wish to venture into the Chinese construction market.